Influence of the Characteristics of Expandable Graphite on the Morphology, Thermal Properties, Fire Behaviour and Compression Performance of a Rigid Polyurethane Foam - Acuña, Pablo (Polymers (Basel), 2019)
Three types of expandable graphite (EG) differing in particle size and expansion volume, are compared as flame retardant additives to rigid polyurethane foams (RPUFs). In this paper we discuss microstructure, thermal stability, fire behavior, and compression performance. We find that ell size distributions were less homogeneous and cell size was reduced. Furthermore, thermal conductivity increased along with EG loading. Thermogravimetric analysis (TGA) showed that EG only increased residue yield differently. The results indicate that a higher expansion of EG increased the limiting oxygen index (LOI) value, whereas a bigger particle size EG improved the rating of the vertical burning test (UL94). Results from the cone calorimeter test showed that a bigger particle size EG effectively reduced peak of heat release rate (pHRR). Furthermore, a higher expansion, led to a decrease in smoke production (TSP). The combination of both characteristics gives extraordinary results. The physical–mechanical characterization of the EG/RPUF foams revealed that their compression performance decreased slightly, mostly due to the effect of a bigger size EG.